Dimensions of development : analysis of an underdeveloped state - Prasad, K. N. (Kedar Nath), 1927- (New Delhi : Concept Pub. Co., 1998)
Comparative study of Bihar and all-India.
v. 1. Agriculture
Includes bibliographical references (v. 1, p. [531]-[533]) and index.
Keywords: Land use, Rural -- India -- Bihar; Agriculture -- Economic aspects -- India -- Bihar; Agricultural credit -- India -- Bihar